2016
DOI: 10.1002/anie.201602763
|View full text |Cite|
|
Sign up to set email alerts
|

Digital Quantification of DNA Replication and Chromosome Segregation Enables Determination of Antimicrobial Susceptibility after only 15 Minutes of Antibiotic Exposure

Abstract: Rapid antimicrobial susceptibility testing (AST) would decrease misuse and overuse of antibiotics. The “holy grail” of AST is a phenotype-based test that can be performed within a doctor visit. Such a test requires the ability to determine a pathogen’s susceptibility after only a short antibiotic exposure. Herein, digital PCR (dPCR) was employed to test whether measuring DNA replication of the target pathogen through digital single-molecule counting would shorten the required time of antibiotic exposure. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 49 publications
2
84
0
Order By: Relevance
“…While the AST technologies described above detect physical and morphological features of bacteria, tools that measure molecular and biochemical signatures, such as changes in 16s RNA 28, 45, DNA 46, 47 and ATP 29, of growing bacterial cells have also been studied. A biosensor-based AST (b-AST) assay being developed by Genefluidics measures bacterial growth via quantitating 16s rRNA molecules, which are specific for each bacterial species 28, 45.…”
Section: Emerging Technologiesmentioning
confidence: 99%
“…While the AST technologies described above detect physical and morphological features of bacteria, tools that measure molecular and biochemical signatures, such as changes in 16s RNA 28, 45, DNA 46, 47 and ATP 29, of growing bacterial cells have also been studied. A biosensor-based AST (b-AST) assay being developed by Genefluidics measures bacterial growth via quantitating 16s rRNA molecules, which are specific for each bacterial species 28, 45.…”
Section: Emerging Technologiesmentioning
confidence: 99%
“…8 While PCR and other genomic amplification techniques are rapid and work well for the high concentrations found in urine, [9][10][11] they are often ineffective in blood samples due to interfering agents and degradative enzymes. 8 While PCR and other genomic amplification techniques are rapid and work well for the high concentrations found in urine, [9][10][11] they are often ineffective in blood samples due to interfering agents and degradative enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Because the bacterial concentration in BSIs is extremely low (often between 1 and 100 CFU/ml 6,7 ), growth amplification is required for most diagnostics. 8 While PCR and other genomic amplification techniques are rapid and work well for the high concentrations found in urine, [9][10][11] they are often ineffective in blood samples due to interfering agents and degradative enzymes. 12 Our proposed diagnostic process described herein requires only 7 ml of blood, a typical volume collected in vacutainer tubes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ismagilov’s group has recently employed dPCR to measure DNA replication of the target pathogen and demonstrated that their digital AST (dAST) can determine the susceptibility of clinical isolates from urinary tract infections (UTIs) after only 15 min of exposure to clinically relevant antibiotics. 113 Another general issue associated with PCR is contamination from non-pathogenic bacterial species (e.g., staphylococcal) introduced during the testing process, as well as from background bacterial nucleic acid materials that exist in PCR reagents (e.g., Taq polymerase) that are manufactured using bacterial sources. 114 Careful screening of vendors and using methods that remove or suppress contaminations are often required to achieve robust PCR performance, especially for detecting low-abundance targets.…”
Section: Emerging Microtechnologies and Automated Systems For Moleculmentioning
confidence: 99%